Berlin Workshop Series 2004 : Service Provision for the Poor--Public and Private Sector Cooperation - Kochendörfer-Lucius, Gudrun (Washington, DC, 2013)
The articles in this volume were presented at the fifth annual Berlin Workshop, held in July 2002, and sponsored by InWEnt-Capacity Building International, Germany, established in 2002 through a merger of the German Foundation for International Development and Carl Duisberg Gesellschaft, and the World Bank. The workshop series is intended as a forum for the research community to contribute to early discussions in preparation for the World Bank's annual World Development Report. Furthermore, the workshop series exposes initial ideas for upcoming World Development Reports-ideas whose policy implications may not yet be entirely clear-to recent thinking by European and other economists and key policymakers outside the Bank. Participants at the 2002 workshop came from a range of research, academic, and policymaking institutions in Europe, the United States, and developing countries as well as the World Bank and German development institutions and organizations. The workshop investigated how countries could accelerate progress toward the Millennium Development Goals by making services work for people living in poverty. The participants hailed successful innovations; took a hard look at some of the failures; and drew conclusions about how to learn from both in order to guide policymakers, donors, and citizens on ways to improve the delivery of basic services: health, education, and water. Making services work for poor people is also the theme of the World Development Report 2004.